Understanding the essence of Islamic civilization: An analysis - Ali, Md Yousuf (2016)
The concept, ‘essence of civilization’ is understood as a set of standard norms or values, which influence man’s conduct, behavior, attitude, and lifestyle. In Muslim history, it has espoused in every sphere of human life. In contemporary Muslim society, widespread unethical practices and their negative consequences pose a strategic threat against the religious value, moral conduct, stability and well-being of Muslim society. It has become a contradictorial trend in the contemporary Muslim community, while the unethical values have been practised by some Muslims as an organ of the culture and civilization. Instances of unethical values and controversial trends can be found in the contexts of free-mixing, making unethical decisions for self-interest and self protection and conflicting values in working places. The paper therefore examines the meaning, purpose, and essence of civilization, and analyzes these within purview of contemporary Islamic thought which is based on the textual arguments of the Qur`an and Sunnah.The paper concludes that though a tiny fraction of the whole Muslim spectrum tries to justify their practices as a reality, the majority of the Muslim scholars has viewed those practices as controvertial and unethical and therefore vehemently argues this civilization to be rectified.